KAJIAN YURIDIS PEMBERATAN SAKSI PIDANA KEPADA PELAKU PEMERKOSAAN DISERTAI PEMBUNUHAN ANAK Studi Putusan Pengadilan Negeri Selong No 55/PID.SUS/2019/PN.SEL - M. Zainuddin; Wirasandi (LPPM Universitas Gunung Rinjani, 2021)
Tujuan penelitian ini adalah untuk mengetahui dasar pertimbangan hukum Majelis Hakim Pengadilan Negeri Selong menjatuhkan pidana penjara selama 20 tahun terhadap pelaku pemerkosa anak disertai pembunuhan dalam putusan perkara pidana khusus No. 55/Pid.SUS/2019/PN.SEL. Metodologi penelitian, jenis penelitian ini adalah yuridis normatif dengan metode pendekatan perundang-undangan (statute aproach). Analisis data mengunakan diskriptif kualitatif yaitu menggambarkan data dari bahan hukum yang diperoleh sesuai dengan permasalahan. Bahan Hukum yang digunakan adalah bahan hukum primer. Hasil penelitian, Pertimbagan hukum Majelis Hakim pada dasarnya menyatakan : 1) perbuatan terdakwa telah terbukti secara sah dan menyakinkan melakukan tindak pidana sebagaimana dalam dakwaan alternatif kesatu yaitu melanggar Pasal 81 ayat 5 (lima) undang-undang Republik Indonesia Nomor 17 Tahun 2016 Tentang Penetapan peraturan pemerintah pengganti Undang-undang Nomor 1 Tahun 2016 tentang Perubahan Kedua atas Undang-undang Nomor 23 tahun 2002 Tentang Perlindungan Anak menjadi Undang-undang Jo. Pasal 76 D Undang-undang Republik Indonesia Nomor 35 Tahun 2014 Tentang perubahan atas Undang-undang Nomor 23 Tahun 2002 Tentang perlindungan anak Jo. Pasal 55 ayat (1) kesatu KUH Pidana. 2) perbuatan terdakwa dilakukan dengan unsur kesengajaan. 3) perbuatan terdakwa menyebakan korban meninggal dunia. 4) perbuatan terdakwa meresahkan masyarakat. Kesimpulan, Majelis Hakim menjatuhkan pidana penjara selama 20 tahun terhadap terdakwa pemerkosa anak disertai pembunuhan adalah perbuatan terdakwa merupakan perbuatan pengabungan antara pemerkosaan dan pembunuhan dengan kesengajaan. Kata kunci : Tindak Pidana, Terdakwa, Anak dan Putusan Pengadilan JURIDICAL REVIEW OF THE ENFORCEMENT OF CRIMINAL WITNESSES TO PERPETRATORS OF RAPE ACCOMPANIED BY MURDER OF CHILDREN Study The Verdict of Selong District Court No. 55 /PID. SUS/2019/PN. SEL By: M. Zainuddin1) and Wirasandi2) 1) Lecturer of Faculty of Law, Gunung Rinjani University, 2) Lecturer of FKIP Accounting Education Study Program of Gunung Rinjani University Email: m.zainuddin1974@gmail.com, Email:sandiwira05@gmail.com ABSTRACT The purpose of this research is to find out the legal basis of the Panel of Judges of Selong District Court sentenced to 20 years imprisonment for child rapists accompanied by murder in the special criminal case verdict No. 55/Pid.SUS/2019/PN. Cell. Research methodology, this type of research is juridical normative with the method of statutory approach (statute approach). Data analysis using qualitative descriptive that describes data from legal materials obtained in accordance with the problem. Legal materials used are primary legal materials. The results of the study, the legal division of the Panel of Judges basically stated: 1) the defendant's actions have been proven legally and convincingly committed a criminal act as in the first alternative indictment that violates Article 81 paragraph 5 (five) of the Law of the Republic of Indonesia Number 17 the Year 2016 concerning the Establishment of government regulation in lieu of Law No. 1 of 2016 concerning the Second Amendment to Law No. 23 of 2002 concerning Child Protection into Law Jo. Article 76 D of the Law of the Republic of Indonesia Number 35 of 2014 concerning amendments to Law No. 23, 2002 concerning the protection of children Jo. Article 55 paragraph (1) of the Criminal Code. 2) The defendant's actions were carried out by the element of willfulness. 3) the defendant's actions resulted in the death of the victim. 4) The defendant's actions unsettled the community. In conclusion, the Panel of Judges sentenced to 20 years imprisonment for the accused child rapist accompanied by murder is the act of the defendant is an act of connection between rape and murder by accident. Keywords: Crimes, Defendants, Children, and Court Decisions